2023
DOI: 10.1049/nbt2.12113
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of ORMDL3 prevents Alzheimer's disease through ferroptosis by PERK/ATF4/HSPA5 pathway

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease with high incidence and widespread attention. There is currently no clear clarification of the pathogenesis. However, ORMDL3 causes ferroptosis in AD, and the potential mechanisms remain unclear. So, this study explore the function of ORMDL3 on ferroptosis in AD and its potential regulatory mechanisms. APPswe/PS1dE9 mice and C57BL/6 mice were induced into the mice model. The murine microglial BV‐2 cells also were induced into the vitro model. In serum sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These results suggest that in our experimental systems these two ferroptosis-inducing agents do not activate the UPR. Although both the PERK-eIF2α-ATF4 and ATF6 branches of the UPR have been implicated in the regulation of ferroptosis with diverse cellular context and inducing agents [48][49][50][51][52][53][54][55][56][57][58][59][60] , we found that when the expression of the key transcription factors of the three UPR branches, XBP1, ATF4 and ATF6 was inhibited individually in MDA-MB-231 cells, ferroptosis induction by erastin treatment was not affected (Fig. 2B-D).…”
Section: Discussionmentioning
confidence: 77%
“…These results suggest that in our experimental systems these two ferroptosis-inducing agents do not activate the UPR. Although both the PERK-eIF2α-ATF4 and ATF6 branches of the UPR have been implicated in the regulation of ferroptosis with diverse cellular context and inducing agents [48][49][50][51][52][53][54][55][56][57][58][59][60] , we found that when the expression of the key transcription factors of the three UPR branches, XBP1, ATF4 and ATF6 was inhibited individually in MDA-MB-231 cells, ferroptosis induction by erastin treatment was not affected (Fig. 2B-D).…”
Section: Discussionmentioning
confidence: 77%
“…HSPA5, a marker of ER stress associated with AD, 41,42 has been shown to interact in vitro with Aβ and tau, mitigating their toxicity. [43][44][45][46][47] Although in vivo studies have identified it as a candidate therapeutic target 48,49 , the detailed mechanisms of action and its relevance in the Aβ-tau interaction are not fully understood. 50…”
Section: Stress Response Factors Moderate Amyloid β-Tau Interactionsmentioning
confidence: 99%
“…[ 176 ] ORMDL3 gene, a susceptibility gene closely related to the occurrence of childhood asthma, promote AD through inducing ferroptosis by PERK/ATF4/HSPA5 signaling pathway. [ 177 ]…”
Section: Ferroptosis In Neurological Diseasesmentioning
confidence: 99%
“…[176] ORMDL3 gene, a susceptibility gene closely related to the occurrence of childhood asthma, promote AD through inducing ferroptosis by PERK/ATF4/HSPA5 signaling pathway. [177] The Role of LPO in AD: The mammalian brain is inadequately equipped with antioxidant defense systems and is prone to oxidative damage due to its high O 2 consumption, and neuronal membrane lipids rich in high PUFAs side-chains, especially DHA (C22:6) residues, [178] Iron is found throughout the brain, [28,179,180] neuronal mitochondria generate O 2…”
Section: Alzheimer's Diseasementioning
confidence: 99%